Surgical quality improvement programs in Japan and USA: Report from the collaborative projects between Japanese Society of Gastroenterological Surgery and American College of Surgeons National Surgical Quality Improvement Program. Issue 4 (22nd April 2019) - Marubashi, Shigeru; Liu, Jessica Y.; Miyata, Hiroaki; Cohen, Mark E.; Ko, Clifford Y.; Seto, Yasuyuki; Gotoh, Mitsukazu
Abstract: The Japanese Society of Gastroenterological Surgery (JSGS) and the American College of Surgeons National Surgical Quality Improvement Program (ACS‐NSQIP) have collaboratively developed several clinical projects since 2011 using two nationwide clinical registries with the goal of achieving further improvement of surgical quality in both countries. In this review, the historical viewpoints and the collaboration between JSGS and ACS and their use of nationwide registries [National Clinical Database (NCD) and NSQIP] for research are reviewed. We have carried out a joint project, the 30‐day Mortality Risk Model Study and, currently, we are working on several joint projects such as the Morbidity‐Mortality Study, Japan‐USA Calibration Study, Geriatric Study, and Safety Culture Study as well as Auditing in JSGS/NCD with reference to the NSQIP method. These joint projects will continue to provide us with important information and data to drive improvements in surgical care in both countries. This will also help us to identify any unknown weaknesses in the health‐care systems of the USA and Japan. Abstract : The Japanese Society of Gastroenterological Surgery (JSGS) and the American College of Surgeons National Surgical Quality Improvement Program (ACS‐NSQIP) have collaboratively developed several clinical projects since 2011 using two nationwide clinical registries with the goal of achieving further improvement of surgical quality in both countries.